Urbanisation, Slums and Incidence of COVID-19: Undertaking Reforms - Pethe, Abhay and Sharma, Rashmi (Nagarlok)
COVID-19 being the headliner of the year 2020, in the absence of a vaccine or medication, has engulfed the whole world. In India, though the lockdown was conceived as a response at a very early stage, the number of cases have multiplied more than 1000 times since then. Data emerging since shows that the outbreak is primarily urban and given the life conditions in the Indian urban areas in general and slums in particular, there had to be a connect between urbanisation, slums and the incidence of COVID-19. The following note first establishes the above-mentioned fact with special focus on slums. In managing the spread of the virus and taking effective measures in responding to its spread, the vulnerabilities of these ever-expanding cities/ slums have been exposed, once again emphasising the need for higher investments in public health, improvement in the state of the slums and eventual creation of affordable houses, more than ever.- Reproduced
Keywords: COVID-19, Governance, Public health infrastructure, Slums, Urbanisation